OPTIMISASI PERIKLANAN DIGITAL: PELATIHAN GOOGLE ADSDAN FACEBOOK ADSBAGI SISWA SMK NEGERI 1 DENDANG - Maisusanto, Eko; Desmayani, Ni Made Mila Rosa; Rahayu, Ni Made Astini; Pratiwi, Ni Wayan Anggita Dara; Prayana, I Kadek Wira Dharma (Yayasan Lavandaia Dharma Bali, 2025)
This community service training program aimed to enhance the digital marketing competencies of vocational high school students through Google Ads and Facebook Ads. The training addressed students’ low understanding of productive digital media use for entrepreneurship. A five-stage method was employed: preparation, pre-test and initial survey, theoretical and hands-on training, guided independent projects, and evaluation. Twenty students participated, and pre-test results indicated limited familiarity with digital advertising concepts (e.g., CPC, CTR, audience targeting). After the practice-based training, knowledge improved significantly, with average post-test scores over 30% higher than pre-test. Participants successfully created simulated ad campaigns, defined target markets, wrote ad copy, set budgets, and evaluated campaign performance. The training not only improved technical skills but also fostered an entrepreneurial mindset, as many students expressed interest in applying digital advertising strategies to personal ventures. In conclusion, the program effectively increased students’ digital marketing literacy and practical skills, aligning with industry needs. It is recommended that digital marketing content be integrated into the school curriculum and similar training be conducted regularly with broader stakeholder support to ensure sustainable impact.